PHARMACOKINETIC PROFILE OF METFORMIN HYDROCHLORIDE IN DRIED BLOOD SPOT OF HEALTHY SUBJECTS USING HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY–PHOTODIODE ARRAY - Harahap, Yahdiana; Malia, Citra Dara; ., Sunarsih (International Journal of Applied Pharmaceutics, 2018)
Objective: This study aimed to analyze the metformin hydrochloride in dried blood spot (DBS) sample and evaluate a pharmacokinetic profile in six healthy subjects who administered 850-mg metformin hydrochloride in tablet using high-performance liquid chromatography–photodiode array (HPLC–PDA). Methods: Metformin analysis was performed on data of six healthy subjects who administered 850 mg of metformin hydrochloride as tablets. Blood samples were taken at 12-time points at intervals of up to 12 h, and data were analyzed using HPLC–PDA. Results: A linear calibration curve was obtained in the range of 25–5000 ng/mL, with r=0.9990. Pharmacokinetic profiles of metformin were obtained using DBS samples from six healthy participants, with a Cmax of 347.3–416.22 ng/mL. The average tmax and t1/2 were obtained at 3 and 2 h, respectively, and the area under the curve (AUC)0-t/AUC0-∞ ratio was >80% for all subjects. Conclusion: The DBS biosampling technique can be developed for application in pharmacokinetic study of metformin HCl.